Assessing chronic and climate‐induced water risk through spatially distributed cumulative deficit measures: A new picture of water sustainability in India. Issue 4 (25th April 2013) - Devineni, Naresh; Perveen, Shama; Lall, Upmanu
Key Points Spatially distributed measure of water stress integrates supply and demand Metric assesses risk posed by within year and over-year variations in supply Much of the water concerns could be alleviated without significant modifications